2021
DOI: 10.1016/j.rmed.2020.106275
|View full text |Cite
|
Sign up to set email alerts
|

Association of inhaled and systemic corticosteroid use with Coronavirus Disease 2019 (COVID-19) test positivity in patients with chronic pulmonary diseases

Abstract: Background The effects of chronic inhaled and systemic corticosteroids use on COVID-19 susceptibility and severity are unclear. Since many patients with chronic pulmonary diseases rely on corticosteroids to control disease, it is important to understand the risks of their use during the pandemic. We aim to study if the use of inhaled or systemic corticosteroids affects the likelihood of developing COVID-19 infection. Methods We used the National Jewish Health electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…The method has been shown to achieve high performance under different configurations, 37,38 and, recently, it has been successfully used in estimating the relationship between use of specific drugs and COVID-19 outcomes. [39][40][41] Specifically, the propensity score for being exposed to a drug was estimated by a multivariable logistic regression model using age, sex, race, ethnicity, and weighted Elixhauser comorbidity score. Using the estimated propensity score, a weighted multivariable logistic regression was performed to estimate the effect of drug exposure on both primary and secondary outcomes, where each patient was weighted with the probability of the patient being assigned to the opposite exposure group.…”
Section: Discussionmentioning
confidence: 99%
“…The method has been shown to achieve high performance under different configurations, 37,38 and, recently, it has been successfully used in estimating the relationship between use of specific drugs and COVID-19 outcomes. [39][40][41] Specifically, the propensity score for being exposed to a drug was estimated by a multivariable logistic regression model using age, sex, race, ethnicity, and weighted Elixhauser comorbidity score. Using the estimated propensity score, a weighted multivariable logistic regression was performed to estimate the effect of drug exposure on both primary and secondary outcomes, where each patient was weighted with the probability of the patient being assigned to the opposite exposure group.…”
Section: Discussionmentioning
confidence: 99%
“…The method has been shown to achieve high performance under different configurations, 23 and, recently, it has been successfully used in estimating the relationship between use of specific drugs and COVID‐19 outcomes. 24 , 25 Specifically, the propensity score for being exposed to a drug was estimated by a multivariable logistic regression model using age, sex, race, ethnicity, and weighted Elixhauser comorbidity score. Using the estimated propensity score, a weighted multivariable logistic regression (adjusted for drug exposure, age, sex, race, ethnicity, and weighted Elixhauser comorbidity score) was performed to estimate the effect of drug exposure on both primary and secondary outcomes, where each patient was weighted with the probability of the patient being assigned to the opposite exposure group.…”
Section: Methodsmentioning
confidence: 99%
“…The risk was reduced although not normalized when adjusted for comorbidities and demographic factors [ 62 ]. Finally, a recent retrospective observational study from Colorado, USA, reported no effect of ICS on rates of testing positive for SARS-CoV-2 [ 25 ]. The authors did report a lower rate of SARS-CoV-2 positivity in patients on systemic corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Currently there are very few studies analyzing the safety and efficacy of ICS in patients with COPD in regards to COVID-19 infection rate or disease severity [ 23 25 ]. We hypothesized that amongst patients with COPD who develop COVID-19, those who are on ICS therapy will have similar inpatient outcomes, mortality and healthcare utilization as those who are not on ICS.…”
Section: Introductionmentioning
confidence: 99%